Evaluation of Amide Proton Transfer‐Weighted Imaging for Lung Cancer Subtype and Epidermal Growth Factor Receptor: A Comparative Study With Diffusion and Metabolic Parameters. Issue 4 (8th March 2022) - Meng, Nan; Fu, Fangfang; Feng, Pengyang; Li, Ziqiang; Gao, Haiyan; Wu, Yaping; Zhang, Jiawen; Wei, Wei; Yuan, Jianmin; Yang, Yang; Liu, Hui; Cheng, Jianjian; et al.
Abstract : Background: Lung cancer is one of the most devastating diseases worldwide, and it is meaningful to assess the subtype and epidermal growth factor receptor (EGFR) status in lung cancer noninvasively by imaging methods. Purpose: To differentiate noninvasively small cell lung cancer (SCLC) from nonsmall cell lung cancer (NSCLC), and EGFR mutation‐type from wild‐type NSCLC by comparing amide proton transfer‐weighted imaging (APTWI), diffusion‐weighted imaging (DWI), and 2‐[ 18 F]‐fluoro‐2‐deoxy‐d ‐glucose positron emission tomography ( 18 F‐FDG PET). Study Type: Prospective. Population: A total of 99 patients with lung cancer. Field Strength/Sequence: APTWI and DWI at 18 F‐FDG PET/MRI 3.0 T. Assessment: The apparent diffusion coefficient (ADC), magnetization transfer ratio asymmetry (MTRasym [3.5 ppm]), maximum standardized uptake value (SUVmax ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were calculated and compared. Statistical Tests: Individual sample t ‐test, Mann–Whitney U test, Logistic regression, and P  < 0.05 were considered statistically significant. Results: In NSCLC, MTRasym (3.5 ppm), MTV, and TLG were significantly lower and ADC was significantly higher than in SCLC; MTRasym (3.5 ppm) was significantly higher and SUVmax, MTV, and TLG were significantly lower in EGFR mutation‐type NSCLC than in EGFR wild‐type NSCLC. In the identification of SCLC and NSCLC, MTRasym (3.5 ppm), ADC, and MTV were independent predictors, the AUCs of the combination of independent predictors, MTV, TLG, MTRasym (3.5 ppm), and ADC were 0.942, 0.875, 0.843, 0.814, and 0.687, respectively. In the identification of EGFR mutation‐type and wild‐type NSCLC, MTRasym (3.5 ppm) and MTV were independent predictors, the AUCs of the combination of independent predictors, TLG, MTV, MTRasym (3.5 ppm), and SUVmax were 0.919, 0.834, 0.813, 0.795, and 0.771, respectively. Data Conclusion: In the noninvasive assessment of lung cancer subtype and EGFR status, APTWI has similar utility to diffusion and metabolic parameters. Level of Evidence: 2 Technical Efficacy Stage: 2